BUDIDAYA MAGGOT DALAM RANGKA MENGURANGI SAMPAH ORGANIK DI DESA BAYAN KECAMATAN BAYAN KABUPATEN LOMBOK UTARA - Sani, Ahmad Luqman; Aeni, Nurul; Swari, Denda Regina; Pratiwi, Elsa; Rahmatullah; Ulla, Lalu Dattur Aqobatil; Fitriani, Nova; Asmita, Yeni; Harley, Goni Assyidiqy (Jurnal Wicara, 2024)
Bayan Village is administratively located in Bayan District, North Lombok Regency, West Nusa Tenggara Province. Bayan Village consists of 9 hamlets which have recently expanded into 13 hamlets including East Bayan Belek Hamlet, West Bayan Belek Hamlet, Karang Salah Hamlet and Bumantar Hamlet with territorial boundaries to the north of Karang Bajo Village, to the east of Loloan Village, to the south National Park Forest Area, west of Senaru Village. Most of the people work as farmers and breeders and Bayan Village also has potential in the tourism sector, most of its area is used as agricultural land so that some of the people work as farmers and breeders. What is grown in Bayan Village is rice, corn, sticky rice, chilies, etc. Apart from being farmers, the people in Bayan Village have several livestock, namely chickens and cows. Almost all people in Bayan Village have chickens and cows. The large amount of waste generated in the form of livestock waste, etc. can disturb the comfort and health of the surrounding community. So the main work program offered is Maggot Cultivation.